Planning for Integrating Teaching Technologies - Mandie Aaron; Dennis Dicks; Cindy Ives; Brenda Montgomery (The Canadian Network for Innovation in Education (CNIE), 2004)
Teaching technologies offer pedagogical advantages which vary with specific contexts. Successfully integrating them hinges on clearly identifying pedagogical goals, then planning for the many decisions that technological change demands. In examining different ways of organizing this process, we have applied planning tools from other domains - Fault Tree Analysis and Capability Maturity Modeling- at the school and college levels. In another approach, we have examined attempts to broadly model the integration process at the university level. Our studies demonstrate that the use of a variety of tools and techniques can render the integration of teaching technologies more systematic.